Non Dispersive Chemical Deacidification of Crude Palm Oil in Hollow Fiber Membrane Contactor - Purwasasmita, Mubiar; Nabu, Eryk Bone Pratama; Khoiruddin, K.; Wenten, I Gede (ITB Journal Publisher, LPPM ITB, 2015)
Performance of chemical deacidification of crude palm oil (CPO) using aqueous NaOH solution in a polysulfone hollow fiber ultrafiltration membrane wasÂ investigated. The effects of operating temperature, NaOH concentration and flow rates on percentage of free fatty acids (FFA) removal, oil loss, soap entrainment and overall mass transfer coefficientÂ wereÂ evaluated. Overall mass transfer coefficients, soap content in oil and neutral oil loss all increasedÂ when theÂ temperatureÂ was increased from 60 to 70Â°C due to an increase of the FFA distribution value. A minimum 0.25 N of NaOH or a NaOH to FFAÂ molar ratioÂ of about 7.62 wasÂ required to facilitate the expected extraction efficiency. The increased oil flowrate slightly enhanced the solute transport kinetics,Â while theÂ aqueous phase flowrate did not significantly influence deacidification efficiency or mass transfer coefficient. About 97% of FFA removal was achieved within 4 hours. The maximum oil loss observed was 11% and the highestÂ soap content in theÂ oil without separation step was 3150 ppm. The valuesÂ of theÂ overall mass transfer coefficient variedÂ from 2.97Ã10-7 to 7.71Ã10-7 m/s. These results show the potential of using the non dispersive membrane contacting process for chemical deacidification of CPO as well as other vegetable oils.